The Terror Courts - JESS BRAVIN (Yale University Press, 2013)
Checkpoints were common as potholes on the roads of Afghanistan. Salim Ahmed Salim Hamdan, driving north on Highway 4 in a Toyota hatchback, was not surprised to be stopped by a group of armed men as he approached the fortified town of Takht-e Pol. Afghanistan was at war. It had been at war for decades. On October 7, less than a month after terrorist attacks obliterated the Twin Towers in New York and destroyed part of the Pentagon in Washington, the United States had become the latest entrant in the Afghan wars. American air strikes and Special Forces backed a loose confederation of militias hostile to the ruling Taliban movement, but here, in Kandahar province, the Taliban still dominated. The city of Kandahar, according to legend founded by Alexander the Great, was the home of Mullah Mohammed Omar, a half-blind cleric who led the Taliban with the aid of Pakistani intelligence. Highway 4 ran southeast from Kandahar to the frontier, into the Pakistani province of Baluchistan and its capital, Quetta. In recent decades, Quetta had been transformed by an influx of Afghan refugees and the elements that inevitably accompanied them: arms dealers, drug smugglers, factional cadre, intelligence agents. The city, which sat just outside the war zone, was a haven for various parties with an interest in Afghanistan. As the American-led campaign turned toward Kandahar, more Afghans would set out along Highway 4 seeking safety in Quetta. But Hamdan was headed the other way: to Kandahar. And to his apparent surprise, the fighters at the checkpoint weren’t Taliban but part of the enemy Pashtun militia. Hours before, American air strikes had blasted out Takht-e Pol’s Taliban defenders, allowing fighters from the eight-hundred-man militia under the warlord Gul Sharzai to enter the town without firing a shot.1 These fighters, nominally loyal to the former king, Mohammed Zahir Shah, were clandestinely obliged to the Central Intelligence Agency.2